Forgiveness Meaning in the Lyric of Gandong Song: Linguistics Point of View - Nikijuluw, Maria Martha; Karuna, Kalvin (Pattimura University, 2021)
This study aims to describe the memorable experience with the conflict, the feelings of the Maluku people, and the influence of the meaning of the lyrics of the Gandong song when listening to the Gandong song, in the context of sustainability of the community’s life Orang Basudara in Maluku. This study used the qualitative method. The primary data were collected using questionnaires with closed and open-ended questions. While literature reviews were about the meaning of the lyrics was collected as secondary data. There were 224 respondents in total, which consist of 53 male respondents and 165 female respondents in the gender category, with 6 people choosing not to identify their gender, and also all from other different backgrounds. Further, the Gandong song, which is a Malukan people's rhythm song, is very popular and frequently sung during conflict and post-conflict times. Subsequently, the result revealed that the respondent listened to the song on several occasions. The lyrics contain a range of word classes, including nouns, verbs, adverbs, adjectives, pronominal phrases, and numerical terms. The term Gandong appears more frequently than other terms. Linguistically means that the song gives stressing on the Gandong relationship as a pearl of important local wisdom for all people living in Maluku. The majority of respondents (99.6 % of 224 respondents) have ever listened to the Gandong song, and it has influenced their feelings about the conflict in Maluku as a reminder of a harmonious life (82. 2%), drawing back from revenge (9, 9%), and 4% of people accepted it to forget the conflict, while the other respondents will forget the feeling of mutual suspicion and forgive rudeness.